Spatial variance analysis of population distribution in Lattakia city - زوان غيثاء (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Population distribution studies are among the most important population studies due to their relevance to all development and planning studies. In light of the rapid population growth in the city of Lattakia and the need for housing, infrastructure and services, it was necessary to study and identify the population centers and shed light on the problem of the high-density rate and the severe variation in the population distribution in the city. The research analyzed the variation in the spatial distribution of the population of the city of Lattakia on an area of ​​4042 hectares divided into 15 neighborhoods, which is equivalent to about 76% of the total area of ​​the actual city, which is 5350 hectares. The studied area includes all neighborhoods of the city except for the northern tourist area and Al Murooj area. The study aims to analyze the population reality in the city and clarify the places of population concentration at the neighborhood level, using SPSS statistical analysis tools and ArcGis geographic information systems techniques, through the Shapiro-Wilk analysis of population densities to test conformity with the natural distribution, and the Lorenz Curve analysis of the relative distribution of the population and the areas of neighborhoods studied, in addition to the preparation of quantitative categories of density maps. The research suggested several methods to represent the variation in population density within the administrative unit, and population center of gravity analysis.